Eco-Friendly Bioprocessing Oil Palm Empty Fruit Bunch (Opefb) Fibers Into Nanocrystalline Cellulose (Ncc) Using White-Rot Fungi (Tremetes Versicolor) and Cellulase Enzyme (Trichoderma Reesei) - Khairul Akli; Maryam Maryam; Maria Isfus Senjawati; Rushdan Ahmad Ilyas (Green Engineering Society, 2022)
The oil palm empty fruit bunch (OPEFB) as solid biomass of palm oil mill industry is available in abundance and has the potential to be utilized as the raw material of nanocrystalline cellulose (NCC). This research aims to investigate the effect of bioprocess treatment (bio-delignification, bio-bleaching, and enzymatic hydrolysis) on the nanocrystalline cellulose synthesized from OPEFB. The bio-delignification of OPEFB fiber was carried out using white-rot fungi (Tremetes versicolor and pre-bleaching pulp with xylanase. Trichoderma reesei, a cellulase enzyme type was used to hydrolyze the OPEFB fiber into nano-sized cellulose. The result exhibits that the cellulose content of OPEFB pulp using bio-delignification increased significantly compared to chemical treatment. Furthermore, the concentration of enzyme and hydrolysis time in the synthesis treatment affect reducing average particle size and increasing the crystallinity index while decreasing the yield of NCC produced. The synthesis process was under optimal processing conditions at 1% enzyme concentration and 3 days of hydrolysis time resulting in the NCC product with 155 nm of average particle size, 66.78% of crystallinity index, and a yield of 38.28%. The bioprocess technology applied in this study could improve the cellulose yield of OPEFB and enhance the quality parameters of NCC products such as particle size and crystallinity index.